Medijski diskurz v Sloveniji in Italiji ter slovensko-italijanskem čezmejnem prostoru v času Covid-19 - Mikolič, Vesna (Monitor ISH, 2021)
This article presents media discourse on health measures during the covid-19 pandemic in Slovenia, Italy and along the Slovenian-Italian border. Based on the corpus method and discursive analysis, we compared discourse practises in traditional and new media and observed the use of new lexemes in the context of pandemics. At the same time, we have highlighted modifications of language intensity, noting how and in what contexts speakers and writers strengthen or weaken the meanings of discourse. We were interested in whether public speech is shaped by positions of power due to social constraints, or whether it aims to promote dialogue, solidarity, and community participation. A comparison of media discourse in Slovenia and Italy showed that public discourse in Italy focuses more on the content of the epidemiological situation and measures, the pandemic is presented as an objective fact, besides the actors of national politics there are different professional groups and other actors, both at national and regional level. In Slovenian discourse, on the other hand, communication is more centralised, largely dependent on state policy and characterised by a higher language intensity. The mutual influence and cooperation of some border media were also highlighted, with special attention paid to the adequacy of public communication for the purposes of cross-border cooperation during difficult border crossings and maintaining intercultural contacts.
Keywords: Covid-19; komunikologija; korpusno jezikoslovje; krizno komuniciranje; Krizno upravljanje; mediji; pandemije